2011
DOI: 10.1007/s11095-011-0529-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Light-Activated RNA Interference Using Phosphorothioate-Based dsRNA Precursors of siRNA

Abstract: Incorporating phosphorothioate groups into dsRNA both stabilizes them towards degradation by serum enzymes, as well as improves them as the basis for light-activated RNA interference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
0
14
0
2
Order By: Relevance
“…One of the possible reasons for the partial inhibition of gene silencing by the photocaged siRNA (35% knockdown without photoirradiation) could be explained by the partial loss of terminal photoreactive units due to nuclease degradation. Friedman et al have first improved their system using phosphorothioate (PS) internucleoside linkages to enhance nuclease resistance near the terminal caged phosphates preventing unwanted loss of the photoreactive moieties before photoirradiation [ 75 ]. This was the case when two PS linkages were introduced into each strand of caged siRNAs.…”
Section: Reviewmentioning
confidence: 99%
“…One of the possible reasons for the partial inhibition of gene silencing by the photocaged siRNA (35% knockdown without photoirradiation) could be explained by the partial loss of terminal photoreactive units due to nuclease degradation. Friedman et al have first improved their system using phosphorothioate (PS) internucleoside linkages to enhance nuclease resistance near the terminal caged phosphates preventing unwanted loss of the photoreactive moieties before photoirradiation [ 75 ]. This was the case when two PS linkages were introduced into each strand of caged siRNAs.…”
Section: Reviewmentioning
confidence: 99%
“…Der Effekt der Nukleobasenmodifizierung auf die Duplexstabilität wurde systematisch untersucht. [152] Eine ähnliche Studie führten Monroe et al mit 2'-Fluor-modifizierten siRNAs durch -sowohl in der Zellkultur als auch in Zebrafischembryonen. Während die Modifikationen des Typs (a), (b) und (d) (Abbildung 6) normalerweise mit geeigneten Bausteinen in der Festphasensynthese hergestellt werden, wird Typ (c) durch eine (unspezifische, statistische) Alkylierung der Oligonukleotide mit einem Diazoderivat der Schutzgruppe erhalten.…”
Section: Andere Anwendungenunclassified
“…Friedman et al reported DNMPE-caged double-stranded siRNAs to photomodulate the silencing of GFP expression without interrupting RFP expression in the cells. 31 33 Using a similar approach, 2′-F substituted siRNAs were caged and their RNAi activities on transient GFP repression were photomodulated in zebrafish embryos with spatial resolution. 41 The number of caging groups per siRNA increased with higher DMNPE diazo concentration.…”
Section: Introductionmentioning
confidence: 99%